Flexural behaviour of reinforced concrete beams with horizontal construction joints. Issue 1 (March 2021) - Al-Rifaie, Ali; Al-Hassani, Hisham; Shubbar, Ali A.
Abstract: In the present research, ten simply supported reinforced concrete beams having a rectangular cross-section were cast and tested up to failure under the action of two-point loads. Eight of these beams were designed to contain horizontal construction joints (HCJs) of different number and location in the beam while the other two beams had no construction joint which were referred to as reference beams for the sake of comparison of results. All the tested beams had been designed to fail in flexure and had the same amount and type of longitudinal and transverse reinforcement as well as similar concrete properties. The results of this series of tests have indicated that the presence of HCJs in reinforced concrete beams leads to a decrease in its ultimate loads and increase in its ultimate deflection. The values of the recorded ultimate loads ranged between 83% to 98% times that of the reference beam while the ultimate deflection ranged between 102% to 133% times that of the reference beam.